Coupled Modeling and Simulation of Phase Transformation in Zircaloy-4 Fuel Cladding Under Loss-of-Coolant Accident Conditions - Lu, Wenjun; Qian, Libo; Zhou, Wenzhong (Frontiers in Energy Research, 2021)
Under loss-of-coolant conditions, the temperature on fuel cladding will increase rapidly (up to 1000–1500 K), which will not only cause a dramatic oxidation reaction of Zircaloy-4 and an increase in hydrogen concentration but also cause an allotropic phase transformation of Zircaloy-4 from hexagonal (α-pahse) to cubic (β-phase) crystal structure. As we all know, thermophysical properties have a close relationship with the microstructure of the material. Moreover, because of an important influence of the phase transformation on the creep resistance and the ductility of the fuel rod, studying the crystallographic phase transformation kinetics is pivotal for evaluating properties for fuel rod completeness. We coupled the phase transformation model together with the existing physical models for reactor fuel, gap, cladding, and coolant, based on the finite element analysis and simulation software COMSOL Multiphysics. The critical parameter for this transformation is the evolution of the volume fraction of the favored phase described by a function of time and temperature. Hence, we choose two different volume fractions (0 and 10%) of BeO for UO2-BeO enhanced thermal conductivity nuclear fuel and zircaloy cladding as objects of this study. In order to simulate loss-of-coolant accident conditions, five relevant parameters are studied, including the gap size between fuel and cladding, the temperature at the extremities of the fuel element, the coefficient of heat transfer, the linear power rate, and the coolant temperature, to see their influence on the behavior of phase transformation under non-isothermal conditions. The results show that the addition of 10vol%BeO in the UO2 fuel decreased the phase transformation effect a lot, and no significant phase transformation was observed in Zircaloy-4 cladding with UO2-BeO enhanced thermal conductivity nuclear fuel during existing loss-of-coolant accident conditions.